Moving beyond Prozac, DSM, & the new psychiatry : the birth of postpsychiatry - Lewis, Bradley, 1956- (Corporealities., 2006)
Annotation "Interesting and fresh-represents an important and vigorous challenge to a discipline that at the moment is stuck in its own devices and needs a radical critique to begin to move ahead."--Paul McHugh, Johns Hopkins University School of Medicine"Remarkable in its breadth-an interesting and valuable contribution to the burgeoning literature of the philosophy of psychiatry."--Christian Perring, Dowling CollegeMoving Beyond Prozac, DSM, and the New Psychiatrylooks at contemporary psychiatric practice from a variety of critical perspectives ranging from Michel Foucault to Donna Haraway. This contribution to the burgeoning field of medical humanities contends that psychiatry's move away from a theory-based model (one favoring psychoanalysis and other talk therapies) to a more scientific model (based on new breakthroughs in neuroscience and pharmacology) has been detrimental to both the profession and its clients. This shift toward a science-based model includes the codification of the Diagnostic and Statistical Manual of Mental Disorders to the status of standard scientific reference, enabling mental-health practitioners to assign a tidy classification for any mental disturbance or deviation. Psychiatrist and cultural studies scholar Bradley Lewis argues for "postpsychiatry," a new psychiatric practice informed by the insights of poststructuralist theory